Climate, conflict, and resilience in Ethiopia: Reflections on the climate security stakeholder workshop - Takaindisa, Joyce; Pacillo, Grazia; Singh, Radhika; Chepngetich, Brenda; Villa, Victor (2025)
Given that a significant population of Ethiopia relies on subsistence agriculture, climate impacts are manifesting in various forms ranging from food insecurity and water scarcity emanating from prolonged droughts, climate induced displacement and migration. Agriculture accounts for between 40 –50% of Ethiopia’s gross domestic product (GDP). Increased competition over scarce resources has intensified such as pastoralist clashes over grazing land.